Bank Risk Taking Behaviour and Performance: Evidence from Indonesian Bank - Anita, Vera; Hanggraeni, Dewi (Dinasti Publisher, 2024)
This study aim to assess the impact of risk management and internal control on Indonesian Banks' risk-taking behaviour and performance. By assessing sample of 60 Banks spanning from 2013 and 2022 using the Generalized Least Square random effect estimator model, results show that while risk management and internal control lower credit risk and operational risk, they have no significant impact on liquidity risk. This impact is more pronounced for Government owned Banks than for privately owned Banks. Furthermore, the research demonstrates that risk management and internal control improve Banks' performance particularly in ROA and ROE parameters.